Regional issues of commercialization of innovative projects and technologies. (Journal of Economic Research & Business Administration, 2015)
The article considered the support of innovative development of the regions, through the establishment of an effective system of innovation support . Created regional commercialization centers (RCC) act as an element of innovation systems , promoting partnerships between scientists , inventors and companies with offices work closely with technology commercialization (OCT). Technology commercialization offices are based on the existing universities, scientific institutes and government enterprises that are actively involved in research activities, directly subordinate to the initiating body.
Keywords: Regional Center of commercialization; commercialization of ideas; innovation support system; offices of technology commercialization; innovative product